Racial discrimination and press in the early 1950s: a portrait of Afonso Arinos Law in its conception and birth - Campos, Walter de Oliveira [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This article makes comments on Law 1390 of 1951, known as Afonso Arinos Law, the first Brazilian law against racial discrimination. The analysis concentrates on the coverage by some large-circulation Brazilian newspapers between 1950 and 1952, period that comprehends the elaboration of the law project, its approval and the immediate repercussion, and that allows to outline the context that shaped the law. This work also brings some comments and analyses on the law by scholars of race relations in Brazil made after the context of creation of the mentioned law. It concludes that the elaboration of Afonso Arinos Law and its portrait by the newspapers were influenced by the predominant view on race relations in Brazil at that time and reflected the ambiguity of a society that supported a discourse of racial harmony and repudiation of racism and discrimination but, in practice, tacitly tolerated racial discrimination.
Keywords: Afonso Arinos Law; Brazilian press; Racial discrimination